OPEN GOVERNMENT DATA AND POLICY INNOVATION IN DIGITAL GOVERNANCE - Thalita Rifda Khaerani; M. Kafrawi Al-Kafiah Samsu (VISIONER : Jurnal Pemerintahan Daerah di Indonesia, 2025)
This study explores the dynamic relationship between open government data (OGD) and policy innovation within the framework of digital governance. As governments worldwide increasingly adopt data-driven decision-making, OGD has emerged as a critical catalyst for enhancing transparency, accountability, and citizen participation. Through a comprehensive literature review, this research synthesizes recent academic contributions that examine how OGD initiatives influence the development of innovative public policies. The analysis highlights the evolving paradigms of data openness, collaborative governance, and digital transformation in the public sector. It identifies key enablers such as technological infrastructure, institutional capacity, and stakeholder engagement that shape the success of OGD-driven policy innovation. Moreover, the study discusses barriers including data quality, interoperability, and privacy concerns that hinder effective implementation. Findings indicate that OGD fosters not only efficiency and trust but also co-creation between citizens and government institutions. This review provides conceptual clarity and strategic insights into how digital governance can leverage OGD to achieve sustainable policy innovation.